Untangling the Knots of Regulatory T Cell Therapy in Solid Organ Transplantation - Orozco, Gabriel; Gupta, Meera; Gedaly, Roberto; Marti, Francesc (Frontiers in Immunology, 2022)
Numerous preclinical studies have provided solid evidence supporting adoptive transfer of regulatory T cells (Tregs) to induce organ tolerance. As a result, there are 7 currently active Treg cell-based clinical trials in solid organ transplantation worldwide, all of which are early phase I or phase I/II trials. Although the results of these trials are optimistic and support both safety and feasibility, many experimental and clinical unanswered questions are slowing the progression of this new therapeutic alternative. In this review, we bring to the forefront the major challenges that Treg cell transplant investigators are currently facing, including the phenotypic and functional diversity of Treg cells, lineage stability, non-standardized ex vivo Treg cell manufacturing process, adequacy of administration route, inability of monitoring and tracking infused cells, and lack of biomarkers or validated surrogate endpoints of efficacy in clinical trials. With this plethora of interrogation marks, we are at a challenging and exciting crossroad where properly addressing these questions will determine the successful implementation of Treg cell-based immunotherapy in clinical transplantation.